Episodio depresivo grave con pensamientos suicidas y su influencia en las relaciones intrafamiliares en un paciente de 30 años de edad - Lopez Almeida, Abel Leonardo (2019)
In this research project a case study is developed, in which the proposal of a psychotherapeutic plan is proposed, which is oriented under cognitive behavioral techniques, developed for the therapeutic intervention of a 30 years old patient, the same as through a psychodiagnostic process, he was diagnosed with a severe depressive episode without psychotic symptoms, influenced by the precarious intrafamily relations In the development of the case study, signs and symptoms manifested by the patient and their clinically significant discomfort will also be described, This also describes the importance of family support in the treatment of the patient, describes in detail the intervention and techniques used, besides, is provided from the point of view of an expert, with a proposal that seeks to be inclusive and effective, in the solution of those similar situations